Genome-Wide Analysis of the PLATZ Gene Family in Oryza Genus: Evolution, Expression During Inflorescence Development and Stress Responses - Hongwei Chen; Xiufang Ma; Guilan Lv; Zheng Wang; Lili Wang; Bowen Yan; Wenqi Shang; Xianju Wang; Zuobin Ma; Wenjing Zheng (Agronomy)
The PLATZ gene family, known for its pivotal roles in regulating plant growth, development, and stress responses, is of great significance in rice biology and crop improvement efforts. In this study, we undertook a comprehensive identification and analysis of the PLATZ gene family across 10 Oryza genus species, including both cultivated and wild rice varieties. A total of 144 PLATZ genes were identified, demonstrating their widespread distribution. Phylogenetic analysis revealed six distinct groups among these genes, with high sequence similarity among members indicating a common evolutionary origin and potential functional conservation. Further analysis of conserved motifs, domains, and promoter regions provided insights into the transcriptional regulation and potential functions of PLATZ genes. Notably, expression profiling showed differential expression patterns of specific PLATZ genes, such as OsPLATZ7, OsPLATZ9, and OsPLATZ11, under various abiotic stress conditions and hormone treatments, highlighting their important roles in stress adaptation and hormone signaling. Additionally, the consistently high expression of OsPLATZ9 across multiple tissues suggests its involvement in multiple developmental processes. Overall, this study provides a detailed characterization of the PLATZ gene family in rice, laying the foundation for future functional studies and potential applications in agricultural biotechnology.